Genome sequences identify three families of Coleoptera as morphologically derived click beetles (Elateridae) - Kusy, Dominik; Motyka, Michal; Bocek, Matej; Vogler, Alfried P; Bocak, Ladislav (Scientific reports, 2018)
Plastoceridae Crowson, 1972, Drilidae Blanchard, 1845 and Omalisidae Lacordaire, 1857 (Elateroidea) are families of the Coleoptera with obscure phylogenetic relationships and modified morphology showing neotenic traits such as soft bodies, reduced wing cases and larviform females. We shotgun sequenced genomes of Plastocerus, Drilus and Omalisus and incorporated them into data matrices of 66 and 4202 single-copy nuclear genes representing Elateroidea. Phylogenetic analyses indicate their terminal positions within the broadly defined well-sclerotized and fully metamorphosed Elateridae and thus Omalisidae should now be considered as Omalisinae stat. nov. in Elateridae Leach, 1815. The results support multiple independent origins of incomplete metamorphosis in Elateridae and indicate the parallel evolution of morphological and ecological traits. Unlike other neotenic elateroids derived from the supposedly pre-adapted aposematically coloured and unpalatable soft-bodied elateroids, such as fireflies (Lampyridae) and net-winged beetles (Lycidae), omalisids and drilids evolved from well-sclerotized click beetles. These findings suggest sudden morphological shifts through incomplete metamorphosis, with important implications for macroevolution, including reduced speciation rate and high extinction risk in unstable habitats. Precise phylogenetic placement is necessary for studies of the molecular mechanisms of ontogenetic shifts leading to profoundly changed morphology.
Keywords: hmyzí proteiny; Insect Proteins; brouci; Molecular Sequence Annotation; Wings, Animal; regulace genové exprese; genom hmyzu; křídla zvířecí; Genome, Insect; Coleoptera; Gene Expression Regulation; Animals; Phylogeny; zvířata; anotace sekvence; fylogeneze